2007 Winter Simulation Conference 2007
DOI: 10.1109/wsc.2007.4419865
|View full text |Cite
|
Sign up to set email alerts
|

Using event simulation to evaluate Internet Protocol enhancements for special services

Abstract: Disasters can cause extraordinary service demand by the public, while concurrently causing outages that reduce network capacity to serve the surging demand. It is imperative that services supporting disaster response management perform with minimal degradation during such events. Mechanisms exist within Internet Protocol (IP)-based networks to provide preferential treatment for services such as voice and video using Differentiated Services Code Points (DSCP) in the packet headers and Per Hop Behaviors in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Therefore, during transmission, packets are assigned DSCP values based on their priority. These values range from 0 to 30 in order of priority level, from 0 default or no priority to 30 high priorities and are categorized as follows: Best Effort (0-0), Class 1 (1-10), Class 2 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and Unknown (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The initial values were defined and it was established that each of these values should remain constant, while others are subject to modification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, during transmission, packets are assigned DSCP values based on their priority. These values range from 0 to 30 in order of priority level, from 0 default or no priority to 30 high priorities and are categorized as follows: Best Effort (0-0), Class 1 (1-10), Class 2 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and Unknown (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The initial values were defined and it was established that each of these values should remain constant, while others are subject to modification.…”
Section: Resultsmentioning
confidence: 99%
“…In their study, Garbin et al [23] demonstrated that IPbased networks incorporate mechanisms to prioritize certain services, such as voice and video, by utilizing DSCPs in packet headers and Per Hop Behaviors in routers. The researchers further examined the advantages of applying additional DSCP markings to voice and video packets, as well as various router configurations.…”
Section: Related Workmentioning
confidence: 99%